The Influence of Customer Experience and Service Quality on Customer Loyalty with Customer Satisfaction as a Mediator: A Study at Kopi Pirak Yogyakarta (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
This study aims to analyze the effect of customer experience and service quality on customer loyalty with customer satisfaction as a mediator. The sample in this research consists of 100 respondents who have visited Kopi Pirak. The data collection technique used is a survey method with a questionnaire as the research instrument. The instrument test results indicate that the statement items show that the convergent validity test meets the required criteria. The results of this study prove that: Customer Experience does not have a significant effect on Customer Loyalty, Service Quality has a positive and significant effect on Customer Loyalty, Customer Experience has a positive and significant effect on Customer Satisfaction, Service Quality has a positive and significant effect on Customer Satisfaction, Customer Satisfaction has a positive and significant effect on Customer Loyalty, Customer Satisfaction has a significant effect in mediating the relationship between Customer Experience and Customer Loyalty, Customer Satisfaction has a significant effect in mediating the relationship between Service Quality and Customer Loyalty. The findings of this study imply that future researchers should test the model using samples with a larger business scale to obtain more varied results. The findings of this study also imply that Kopi Pirak needs to improve customer experience in order to enhance customer loyalty.